2021
DOI: 10.1002/jsfa.11018
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic and enzymatic pretreatments of Monascus fermentation byproduct for a sustainable production of Bacillus subtilis

Abstract: BACKGROUND Monascus fermentation byproduct (MFB) is a biowaste generated after food colorants are extracted. Using MFB to produce probiotics (Bacillus subtilis) is a sustainable way for the entire production to be used as food or animal feed additives. However, due to the rigidity of the Monascus mycelium cell wall, B. subtilis cannot sufficiently utilize the nutrients in MFB, leading to low biomass production efficiency. We studied the effects of ultrasonic treatment, papain, β‐glucanase, and chitosanase, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…To determine the composition of monosaccharides, samples were hydrolyzed by 2 M trifluoroacetic acid solution at 120 °C for 5 h. After hydrolysis, the samples were collected. The neutral monosaccharide composition was determined by gas chromatography (6890 A, Agilent Technologies, Santa Clara, CA, USA) ( Zhang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the composition of monosaccharides, samples were hydrolyzed by 2 M trifluoroacetic acid solution at 120 °C for 5 h. After hydrolysis, the samples were collected. The neutral monosaccharide composition was determined by gas chromatography (6890 A, Agilent Technologies, Santa Clara, CA, USA) ( Zhang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Monascus , a small filamentous saprophytic fungus, plays an important role in household food consumption and industrial food manufacture [ [11] , [12] , [13] ], including the production of rice fermented products [ 14 ], natural colorants [ 15 , 16 ], and medicines [ 17 ]. Zhao et al found that fermented Panax ginseng by Monascus ruber regulated lipid metabolism and intestinal flora structure in high fat diet rats, which reduced obesity characteristics and lowered serum total cholesterol, low-density lipoprotein cholesterol and IgA levels [ 18 ].…”
Section: Introductionmentioning
confidence: 99%